Propionate-oriented kitchen waste fermentation for polyhydroxyalkanoate production by mixed microbial cultures - Xiaolei Zhang; Yingxue Sun; Shaoping Luo; Song Liu; R.D. Tyagi; Hongjie Wang; Ji Li (Bioresource Technology, 2026)

Preparation of N-doped activated carbon from enzymatic hydrolysis lignin using Mannich reaction and H3PO4 activation - Asim Waseem; Yang Li; Shaoping Xu; Kechao Wang; Haoquan Hu (Biomass and Bioenergy, 2026)

Comprehensive prevention and control technologies for karst tunnel construction safety: integration of advanced forecasting, monitoring, and emergency response - Yaodong Luo; Bing Luo; MingJun Li; Tiansi Zhang; Shaoping Yang; Luyao Ma; Bihe Zhang; Haoyan Zhang; Saeed Rehman (Carbonates and Evaporites, 2026)

Quercetin glycoside-specific modulation of the gut-brain axis determines protection against colitis-associated cognitive decline - Ze Tao; Shanfeng Qiao; Wanyu Zhang; Xinke Nie; Ying He; Bingnan Li; Zeyu Xia; Yuhan Li; Qiqiong Li; Junhua Xie; Shaoping Nie (Food Research International, 2026)

Dynamics of a stochastic tumor-immune interaction system with an Ornstein-Uhlenbeck process - Huimin Li; Yin Zhang; Shaoping Jiang; Xuewen Tan (Mathematical Biosciences, 2026)

MOF-derived MgMn-C composites for catalytic ozonation of phenol: Preparation and performance evaluation - Meiyi Hu; Jiaxin Wang; Ziyi Zhang; Donghang Li; Kun-Yi Andrew Lin; Shaoping Tong (Journal of Water Process Engineering, 2026)

In situ sludge reduction assisted by alternating electrode-based electrochemical treatment - Xiaolei Zhang; Quanze Liu; Shaoping Luo; Yingxue Sun; Yong Li; Wenyi Dong; Patrick Drogui; Ji Li (Bioresource Technology, 2026)

A Statistical Quality-Control Framework for Sentinel-1 SAR Wind Speed Retrieval Based on First- and Second-Order Moments - Yan Wang; Xupu Geng; Yan Li; Xiaohui Li; Chenghan Luo; Shaoping Shang; Feng Zhang (Journal of Marine Science and Engineering, 2026)
Synthetic Aperture Radar (SAR) enables high-resolution sea-surface wind speed retrieval. However, the enhanced spatial resolution of SAR imagery introduces substantial challenges, from small-scale contamination sources that significantly degrade retrieval accuracy. Particularly in coastal regions, non-wind-related backscatter signals, such as ships and oil slicks, can severely bias wind speed estimates at sub-kilometer scales. In this study, the first-order moment (average, m1) and second-order moment (variance, m2) are computed from the normalized radar cross-section (NRCS) within sub-images of Sentinel-1 SAR data acquired in Interferometric Wide (IW) mode. Analysis reveals that clean-sea-surface signals in both VV and VH polarizations cluster around an approximately linear empirical trend, m2 = 2m1 + b, in the m1-m2 statistical feature space, whereas the examined contamination types deviate from this trend and occupy separable regions. Based on this characteristic, a quality-control framework is proposed for the systematic separation of clean sea surface from image noise (border noise and inter-swath stripe noise) and non-ocean targets (land contamination, bright targets, and dark spots). Validation using independent SAR data from the Taiwan Strait was conducted separately for native 10 m and height-adjusted 3 m buoy observations. For the native 10 m observations, the RMSE and MBE were essentially unchanged at 1.5 m/s and −0.3 m/s, respectively. For the height-adjusted nearshore observations, the RMSE decreased from 3.2 m/s to 2.1 m/s and the MBE changed from −1.5 m/s to −1.1 m/s.

Polycyclic aromatic compounds in soils from a petrochemical-contaminated site in eastern China: Target and non-target analysis with risk assessment - Yimeng Si; Siyuan Li; Yu Wang; Ruiqi Zhang; Liman Wei; Hao Chen; Yanlong Zhang; Yiming Yao; Shaoping Kuang; Hongwen Sun (Environmental Pollution, 2026)

Synergistic inversion of maize leaf chlorophyll using multi-source remote sensing data - Shaoping Sun; Jixuan Yan; Guang Li; Zichen Guo; Wenning Wang; Qiang Li; Kejing Cheng; Xuchun Li; Jiaqin Yuan; Changbo Wu (Irrigation Science, 2026)

A synbiotic combination of arabinogalactan and Bacteroides thetaiotaomicron ameliorates ulcerative colitis in mice - Shanshan Zhang; Yonggan Sun; Yuhao Li; Chunhua Chen; Shaoping Nie (Food Research International, 2026)

Screening and construction of promoter-5′-untranslated region complex library of Sphingomonas paucimobilis for regulating the metabolic pathway of gellan biosynthesis - Yujia Zhou; Zhiming Li; Xinghui Xie; Xingtao Zhou; Yadong Zhong; Jielun Hu; Shaoping Nie (Bioresource Technology, 2026)

Remodeling of phenolic compounds from celery pulp driven by Lactobacillus plantarum NCU116 fermentation: insights from omics, targeted quantification, and microstructural imaging - Yuhao Li; Yingying Zeng; Weiwei He; Yangyang Xun; Yuxin He; Shuai Liu; Xiaoyi Hu; Xiaoxiao Song; Shaoping Nie; Junyi Yin; Mingyong Xie (Food Research International, 2026)

Strength Degradation and Chloride Ion Diffusion Behavior of Concrete Under Simulated Marine Exposure - Shaoping Li; Xiaozhou Zhang; Yaling Zhao; Hongjun Jing; Ping Lyu; Junwei Shan (Journal of Marine Science and Engineering, 2026)
Chloride-induced deterioration is a major threat to the durability of marine concrete structures, especially in tidal and submerged zones. This study simulated these environments by immersing C45 concrete specimens in NaCl solutions (5%, 10%, 15%) under both constant immersion and wet–dry cycles. Compressive strength tests, low-field NMR for pore structure, chloride ion profiling, and SEM-EDS analyses were conducted. A modified chloride diffusion model was developed based on Fick’s second law, incorporating time- and concentration-dependent parameters. The results showed that higher NaCl concentrations and tidal zone exposure significantly accelerated concrete degradation. In the tidal zone, wet–dry cycles led to larger macropore formation, higher chloride penetration, and more severe microstructural damage compared to the submerged zone. Compressive strength initially increased and then declined in high-salinity environments, with strength losses reaching up to 25% under 15% NaCl after 120 days. NMR data confirmed the transformation of micropores and mesopores into macropores, especially in the tidal zone. SEM-EDS analysis revealed decalcification, gypsum formation, and Friedel’s salt accumulation on eroded surfaces. It was determined that chloride ion diffusion behavior in concrete is significantly influenced by the chloride content and diffusion concentration, as well as the exposure zone. The developed model indicates that depth increased over time and with concentration. The proposed diffusion model achieved high fitting accuracy (R2 > 0.97), effectively capturing the effects of erosion age and salt; this makes it a reliable tool for predicting chloride ion ingress in marine concrete, and for supporting service life evaluation and durability design.

Direct carbon recovery from raw wastewater for bioenergy production by anaerobic digestion - Yingxue Sun; Ji Li; Shaoping Luo; Yinghui Liu; R.D. Tyagi; Xiaolei Zhang (Bioresource Technology, 2026)

Flavor formation and microbial community dynamics in Dong ethnic fermented Anyu - Fenghong Li; Kelang Kang; Qun Huang; Xin li; Shaoping Deng; Yingjuan Wei; Hui Yang; Meijuan Yu (Food Research International, 2025)

Health effects of polyphenols combined with bacteria from the perspective of gut microbiota - Yuhan Li; Xinke Nie; Chen Liu; Qiqiong Li; Shaoping Nie; Mingyong Xie (Food Bioscience, 2025)

Modulation of the gut-skin axis by polysaccharides: Mechanisms and therapeutic potential in immune-related skin diseases - Chen Haiming; Liao Yijing; Tang Bin; Ma Xiaoyu; Li Hailun; Dong Meiting; Li Ziqing; Zheng Xuwei; Yang Yujie; Su Zuqing; Li Shaoping; Lu Chuanjian (Carbohydrate Polymers, 2025)

Purification, structural characterization, and in vitro fermentation properties of okra polysaccharides - Xin Li; Xiaojun Huang; Shaoping Nie (Bioactive Carbohydrates and Dietary Fibre, 2025)

Exploring key genes involved in the biosynthesis of gellan in Sphingomonas paucimobilis based on transcriptomic and metabolomic analyses of UV/ARTP-induced mutants - Yujia Zhou; Zhiming Li; Xinghui Xie; Xingtao Zhou; Jielun Hu; Shaoping Nie (Food Bioscience, 2025)

Integrin α5 is involved in immune defense by regulating hemocyte phagocytosis in shrimp - Lingling Li; Bangping Hu; Zi-ang Wang; Jiefeng Gao; Shaoping Weng; Jianguo He; Xiaopeng Xu; Hongliang Zuo (Fish & Shellfish Immunology, 2025)

P38 MAPK regulates phagocytosis of bacteria and fungi by hemocytes in Macrobrachium rosenbergii - Ran Geng; Bangping Hu; Alian Liao; Lingling Li; Hongliang Zuo; Zhixun Guo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2025)

Mechanistic insights into ornidazole degradation during the sulfidation and reoxidation cycling of ferrihydrite - Guangyu Li; Weijian Liu; Chenhao Wang; Zexu Zhang; Zhiruo Zhang; Rui Fan; Leyun Shi; Guorui Kong; Mengmeng Wang; Shaoping Kuang (Chemical Engineering Journal, 2025)

Advances in mammalian, plant, and bacterial-derived extracellular vesicles for cancer therapy - Xinke Nie; Qiqiong Li; Hina Fatima; Yucheng Wang; Fan Meng; Junhua Xie; Shaoping Nie (Chemical Engineering Journal, 2025)

Celery (Apium graveolens L.) juice fermented with Lactiplantibacillus plantarum NCU116 mitigates type 2 diabetes in mice: Mechanistic insights from gut microbiota and metabolomics - Xiaoyi Hu; Weiwei He; Tuo Leng; Wentao Shen; Shuai Liu; Yuhao Li; Xiaoxiao Song; Shaoping Nie; Junyi Yin; Mingyong Xie (Food Bioscience, 2025)

TRIM22 in Litopenaeus vannamei activates Dorsal by accelerating Cactus's degradation to mediate antiviral immunity - Xuanzheng Di; Hao Yang; Airong Lv; Xiaodi Wang; Ruiying Li; Ranran Wang; Bin Yin; Sheng Wang; Shaoping Weng; Chaozheng Li; Jianguo He; Haoyang Li (Fish & Shellfish Immunology, 2025)

Regulatory Mechanism of CRTC1 on Autophagy and GluA2 Expression in Epilepsy - Xueying Wang; Liqian Zhou; Lin Yang; Shaoping Huang; Yuying Wang; Dan Li (Molecular Neurobiology, 2025)

Supplementation of Akkermansia muciniphila improves diabetic kidney disease by regulating gut microbiome in db/db mice - Zhengzheng Liao; Jian Zhou; Jiaqiang Lin; Yue Zhu; Jing Feng; Zhouyang Cheng; Xiajialong Li; Zhipeng Li; Shaoping Nie (Food Bioscience, 2025)

Dual protection against grouper Rana-Iridovirus (GIV-R) and nervous necrosis virus (NNV) by novel GIV-R-Δ51−NNV-CP chimeric vaccine candidates - Shan Ding; Yong Li; Qianqian Sun; Zhiming Zhu; Fangzhao Yu; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Acute hypoxia stress impairs Litopenaeus vannamei resistance to white spot syndrome virus by downregulating chitin-binding proteins - Honghui He; Shaoping Weng; Chaozheng Li; Jianguo He (Fish & Shellfish Immunology, 2025)

Fermentation of celery (Apium graveolens L.) with Lactobacillus plantarum NCU116: Impact on physicochemical properties, free amino acids, and volatile aroma compounds - Yuhao Li; Weiwei He; Yuxin He; Shuai Liu; Xiaoyi Hu; Shuigen Bian; Xiaoxiao Song; Junyi Yin; Shaoping Nie; Mingyong Xie (Food Bioscience, 2025)

A new strategy for efficient adsorption-low fire risk for oil-water separation remediation without hydrophobic coatings: CoFeNi-PBA catalytic carbonization of melamine sponges - Haopeng Zhang; Gaoyuan Li; Biyu Huang; Jirui Qu; Kailiang Huang; Xilei Chen; Chuanmei Jiao; Shaoping Kuang (Chemical Engineering Journal, 2025)

Acute hypoxia stress decreases the resistance of Litopenaeus vannamei to Vibrio parahaemolyticus infection - Honghui He; Shaoqing Huang; Shaoping Weng; Jianguo He; Chaozheng Li (Aquaculture, 2025)

Ammonia nitrogen stress induces dysbiosis of the intestinal bacterial community and facilitates the enrichment of pathogenic bacteria in intestines of shrimp - Dongwei Hou; Haoyang Li; Sheng Wang; Shaoping Weng; Jianguo He (Aquaculture, 2025)

Reproductive toxicity of bisphenol A and nitro-bisphenol A in male zebrafish at environmentally relevant concentrations - Chao Wang; Shuyi Zhang; Zijin Shao; Peijie Sun; Jiran Zhang; Shaoping Zhang; Jian Kong; Hong Zhi; Li Li; Mingshu Li; Jie Yu; Zhenming Liu; et al. (Science of The Total Environment, 2025)

Seismic Reflection Imaging Reveals Relict Subduction Zone of the Paleo-Pacific Plate in the Northeastern South China Sea - Zongdong Pan; Shaoping Lu; Hongfang Gao; Lun Li; Han Chen; Rui Gao; Qing He (Journal of Asian Earth Sciences, 2024)

Structural characterization and prebiotic activity evaluation of novel fucosylated disaccharides prepared from bacterial exopolysaccharides - Shihao Nan; Xinmiao Ren; Mengshi Xiao; Lin Zhu; Haijin Mou; Ningyang Li; Rong Li; Shaoping Nie; Xiaodan Fu (Food Bioscience, 2024)

Microseisms associated with the southwest summer monsoon recorded on the seafloor of South China Sea - Yulong Zhou; Fansheng Kong; Han Zhang; Zhangju Liu; Xiongwei Niu; Aiguo Ruan; Shaoping Lu; Jianke Fan; Pingchuan Tan; Xiaodong Wei; Weiwei Ding; Jiabiao Li (Earth and Planetary Science Letters, 2024)

Preparation of environmentally friendly ionic liquids-toughened polylactic acid/nanofibrillated cellulose composites with high strength and precipitation resistance - Zhaoyan Zhang; Shaoping Qian; Xinyu Li; Changfa Zhu; Zhijie Li (Chemical Engineering Journal, 2024)

Investigating the Effects of Perampanel on Autophagy-mediated Regulation of GluA2 and PSD95 in Epilepsy - Dan Li; Na Sun; Yingying Guo; Shaoping Huang; Chunyan Yin; Yanfeng Xiao; Weijun Ma (Molecular Neurobiology, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Evaluation of the anti-atherosclerotic effect for Allium macrostemon Bge. Polysaccharides and structural characterization of its a newly active fructan - Pei Lin; Qiqi Wang; Qi Wang; Jiayun Chen; Liangliang He; Zifei Qin; Shaoping Li; Jingyan Han; Xinsheng Yao; Yang Yu; Zhihong Yao (Carbohydrate Polymers, 2024)

BnaPLDα1-BnaMPK6 Involved in NaCl-Mediated Overcoming of Self-Incompatibility in Brassica napus L. - Yuanyuan Li; WenXuan Zhang; Yong Yang; Xiaomei Liang; Shaoping Lu; Chaozhi Ma; Cheng Dai (Plant Science, 2024)

Volatile compound dynamics during blueberry fermentation by lactic acid bacteria and its potential associations with bacterial metabolism - Yuxin He; Mengwei Hu; Weiwei He; Yuhao Li; Shuai Liu; Xiaoyi Hu; Shaoping Nie; Junyi Yin; Mingyong Xie (Food Bioscience, 2024)

Nitrite nitrogen stress disrupts the intestine bacterial community by altering host-community interactions in shrimp - Dongwei Hou; Haoyang Li; Sheng Wang; Shaoping Weng; Jianguo He (Science of The Total Environment, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Efficient stabilization of arsenic migration and conversion in soil with surfactant-modified iron-manganese oxide: Environmental effects and mechanistic insights - Mei Li; Yan Kang; Shaoping Kuang; Haiming Wu; Linlan Zhuang; Zhen Hu; Jian Zhang; Zizhang Guo (Science of The Total Environment, 2024)

Denitration performance and mechanism of Mn-Ce supported alkali-modified fly ash catalysts for NH3-SCR - Pan Zhang; Wohui Yu; Bing Gao; Shaoping Cui; Jingxin Li; Liqiang Qi (Fuel, 2024)

Preliminary Results of the Seismicity Monitoring Experiment around the 2019 Mw5.4 Earthquake Epicenter in the Central South China Sea Basin - Wenfei Gong; Aiguo Ruan; Xiongwei Niu; Zhenjie Wang; Pingchuan Tan; Xiaodong Wei; Wei Wang; Zhengyi Tong; Liqun Cheng; Fansheng Kong; Shaoping Lu; Jianke Fan; et al. (Journal of Earth Science, 2024)

Bacterial extracellular vesicles: An emerging postbiotic - Junhua Xie; Qiqiong Li; Shaoping Nie (Trends in Food Science & Technology, 2024)

Biogeography and diversity patterns of functional genes associated with C, N, P, S cycling processes across China classical sea sediments - Shuai Liu; Xin Huang; Hongyu Mu; Minggang Zheng; Shaoping Kuang; Hui Chen; Yan Xu; Dong Wang; Huan Liu; Xuan Li (Science of The Total Environment, 2024)

The structure of anthocyanins and the copigmentation by common micromolecular copigments: A review - Jiadong Wang; Yanqiao Zhao; Bing Sun; Yutong Yang; Shaoping Wang; Zirui Feng; Jianying Li (Food Research International, 2024)

Aqueous two-phase system based on pH-responsive polymeric deep eutectic solvent for efficient extraction of aromatic amino acids - Changyong Cai; Shaoping Ma; Fenfang Li; Zhijian Tan (Food Chemistry, 2024)

Effects of four food hydrocolloids on colitis and their regulatory effect on gut microbiota - Shanshan Zhang; Yonggan Sun; Qixing Nie; Jielun Hu; Yuhao Li; Zefu Shi; Haihua Ji; Hao Zhang; Mingjiao Zhao; Chunhua Chen; Shaoping Nie (Carbohydrate Polymers, 2024)

Low-dose Lipopolysaccharide Alleviates Spinal Cord Injury-induced Neuronal Inflammation by Inhibiting microRNA-429-mediated Suppression of PI3K/AKT/Nrf2 Signaling - Weichao Li; Tao Tang; Shaoping Yao; Shixiao Zhong; Qianbo Fan; Tiannan Zou (Molecular Neurobiology, 2024)

Changes in volatile and nutrient components of mango juice by different Lactic acid bacteria fermentation - Shuai Liu; Yuhao Li; Xiaoxiao Song; Xiaoyi Hu; Yuxin He; Junyi Yin; Shaoping Nie; Mingyong Xie (Food Bioscience, 2023)

The mediating role of exhaled breath condensate metabolites in the effect of particulate matter on pulmonary function in schoolchildren: A crossover intervention study - Xiaoyan Yang; Dongqun Xu; Bo Wen; Jian Ji; Zeyu Zhang; Li Li; Shaoping Zhang; Hong Zhi; Jian Kong; Chong Wang; Jun Wang; Hongjie Ruan; et al. (Science of The Total Environment, 2023)

Lithospheric velocity structure of South China Sea basin from ocean bottom seismometer ambient noise tomography - Liqun Cheng; Yinxia Fang; Xiongwei Niu; Tingzi Li; Chongzhi Dong; Yanghui Zhao; Hao Hu; Fansheng Kong; Pingchuan Tan; Aiguo Ruan; Shaoping Lu; Jianke Fan; et al. (Tectonophysics, 2023)

A biomimetic design for efficient petrochemical spill disposal: CoFe-PBA modified superhydrophobic melamine sponge with mechanical/chemical durability and low fire risk - Haocun Guan; Rongjia Li; Richeng Lian; Jiahui Cui; Mingyu Ou; Lei Liu; Xilei Chen; Chuanmei Jiao; Shaoping Kuang (Journal of Hazardous Materials, 2023)

Energy analysis of wind-induced wave and current during typhoon kalmaegi - Feng Zhang; Lei Wang; Chongwei Zheng; Kenny Thiam Choy Lim Kam Sian; Shaoping Shang; Hengyou Lan; Zhijie Jiang; Yundong Li; Han Zhang; Zhigang He; Guomei Wei; Yanshuang Xie; et al. (Estuarine, Coastal and Shelf Science, 2023)

Abundance, diversity, and community structure of comammox cladeA in sediments of China's offshore continental shelf - Shuai Liu; Mengxin Xu; Minggang Zheng; Huan Liu; Shaoping Kuang; Hui Chen; Xuan Li (Science of The Total Environment, 2023)

Targeted modification of gut microbiota and related metabolites via dietary fiber - Qixing Nie; Yonggan Sun; Mingzhi Li; Sheng Zuo; Chunhua Chen; Qiongni Lin; Shaoping Nie (Carbohydrate Polymers, 2023)

Efficient removal of heavy metals from aqueous solutions using Mn-doped FeOOH: Performance and mechanisms - Mei Li; Yan Kang; Haoqin Ma; Jiahao Dong; Yuqi Wang; Shaoping Kuang (Environmental Research, 2023)

Interaction between four galactans with different structural characteristics and gut microbiota - Song Li; Jielun Hu; Haoyingye Yao; Fang Geng; Shaoping Nie (Critical Reviews in Food Science and Nutrition, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Persulfate oxidation of tetracycline, antibiotic resistant bacteria, and resistance genes activated by Fe doped biochar catalysts: Synergy of radical and non-radical processes - Mengmeng Wang; Yafei Wang; Yingchun Li; Chenhao Wang; Shaoping Kuang; Peng Ren; Binghan Xie (Chemical Engineering Journal, 2023)

Study on why FeOCl has high Fenton activity in wide range of initial pH and its corresponding stability - Jie Wang; Yujie Li; Qihui Jiang; Shaoping Tong (Process Safety and Environmental Protection, 2023)

Combined biological effects of polystyrene microplastics and phenanthrene on Tubifex tubifex and microorganisms in wetland sediment - Jiahao Dong; Yan Kang; Shaoping Kuang; Haoqin Ma; Mei Li; Jingqian Xiao; Yafei Wang; Zizhang Guo; Haiming Wu (Chemical Engineering Journal, 2023)

Innate immune receptors co-recognition of polysaccharides initiates multi-pathway synergistic immune response - Mingzhi Li; Xiaojun Huang; Jiajia Wen; Shikang Chen; Xincheng Wu; Wanning Ma; Steve W. Cui; Mingyong Xie; Shaoping Nie (Carbohydrate Polymers, 2023)

Dynamic contribution and structural changes of carbon emissions in China’s energy chemical industry with high-emission subsectors heterogeneity - Hengshuo Zhang; Shaoping Li; Bangbo Xiong; Liping Li (Environmental Science and Pollution Research, 2023)

Effectively protecting Asian seabass Lates calcarifer from ISKNV-I, ISKNV-II, RSIV-II and SDDV by an inactivated ISKNV-I and SDDV bivalent vaccine - Yuting Fu; Yong Li; Wenfeng Zhang; Weixuan Fu; Wangdong Li; Zhiming Zhu; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

The removal of antibiotic, antibiotic resistant bacteria and genes in persulfate oxidation system via activating by antibiotic fermentation dregs derived biochar - Yafei Wang; Chenhao Wang; Shen Yan; Yingchun Li; Chen Cai; Huiling Liu; Peng Ren; Mengmeng Wang; Shaoping Kuang (Journal of Cleaner Production, 2023)

Kill three birds with one stone: Mitochondria-localized tea saponin derived carbon dots with AIE properties for stable detection of HSA and extremely acidic pH - Shengtao Zhang; Bin Li; Jieyu Zhou; Jiayi Shi; Zhongjing He; Yumin Zhao; Yan Li; Yehua Shen; Yongmin Zhang; Shaoping Wu (Food Chemistry, 2023)

Antioxidant peptides from edible aquatic animals: Preparation method, mechanism of action, and structure-activity relationships - Zedong Xiang; Qing Xue; Peng Gao; Haitao Yu; Mingze Wu; Zanzan Zhao; Yanan Li; Shaoping Wang; Jiayu Zhang; Long Dai (Food Chemistry, 2023)

Experimental study on a dry-assembled precast concrete frame with buckling-restrained braces - Yuan Qing; Xiuhang Li; Chun-Lin Wang; Bin Zeng; Shaoping Meng (Engineering Structures, 2023)

Investigation on the contents of heat-induced hazards in commercial nuts - Wenting Liu; Yuting Wang; Dechang Xu; Huiyu Hu; Yilun Huang; Yuwei Liu; Shaoping Nie; Chang Li; Mingyong Xie (Food Research International, 2023)

MALDI mass spectrometry in food carbohydrates analysis: A review of recent researches - Junqiao Wang; Jing Zhao; Shaoping Nie; Mingyong Xie; Shaoping Li (Food Chemistry, 2023)

Biochar-amended composting of lincomycin fermentation dregs promoted microbial metabolism and reduced antibiotic resistance genes - Chenhao Wang; Yafei Wang; Shen Yan; Yingchun Li; Peng Zhang; Peng Ren; Mengmeng Wang; Shaoping Kuang (Bioresource Technology, 2023)

Alpha-aminoisobutyric acid incorporated peptides for the construction of electrochemical biosensors with high stability and low fouling in serum - Xiqin Yang; Min Chen; Zhanhua Zhang; Yang Li; Peipei Wang; Xiliang Luo; Shaoping Lv (Analytica Chimica Acta, 2023)

Association between short- and long-term exposures to air pollutants and internalizing/externalizing behavior in children aged 4 to 7 years - Haiqin Qi; Anna Peng; Hong Mei; Yuanyuan Zhang; Ya Zhang; Paiziyeti Tuerxun; Wenli Dong; Chunan Li; Ke Xu; Ruixia Chang; Shaoping Yang; Jianduan Zhang (Environmental Science and Pollution Research, 2022)

Risk Assessment of Wave Over-Topping Based on Smoothed-Particle Hydrodynamics Method - Lei Wang; Li Zhang; Yanshuang Xie; Yaozhao Zhong; Yuan Sun; Zhiyuan Wang; Feng Zhang; Shaoping Shang (Journal of Marine Science and Engineering, 2022)
FETSWCM-SWAN and DualSPHysics models are used to study the storm flooding process of Dazuo Seawall in Quanzhou city, Fujian province, China. Firstly, a storm over-topping assessment method is proposed. Secondly, the water level and storm wave at the foot of Dazuo Seawall calculated by FETSWCM-SWAN during the process of Typhoon Usagi in 2013 and Typhoon Dujuan in 2015. Finally, the typical wave and storm run-up processes at Dazuo Seawall are modeled by DualSPHysics. The results show that the typical wave run-up of Dazuo Seawall is less than 2 m, but the storm wave run-up can reach 6.85 m under Usagi. The risk is high when high tide is encountered. The risk of storm flooding is classified into three grades. This risk assessment could provide decision-making support to government departments in warning against storm flooding threats.

Seismic Shot Gather Denoising by Using a Supervised-Deep-Learning Method with Weak Dependence on Real Noise Data: A Solution to the Lack of Real Noise Data - Xintong Dong; Jun Lin; Shaoping Lu; Xingguo Huang; Hongzhou Wang; Yue Li (Surveys in Geophysics, 2022)

In vitro gastrointestinal digestion and fermentation models and their applications in food carbohydrates - Haihua Ji; Jielun Hu; Sheng Zuo; Shanshan Zhang; Mingzhi Li; Shaoping Nie (Critical Reviews in Food Science and Nutrition, 2022)

USP21 regulates Hippo signaling to promote radioresistance by deubiquitinating FOXM1 in cervical cancer - Zhengliang Li; Xiaojing Liu; Haizhou Yu; Shaoping Wang; Shuliang Zhao; Guoxiang Jiang (Human Cell, 2022)

Hypoglycemic mechanism of polysaccharide from Cyclocarya paliurus leaves in type 2 diabetic rats by gut microbiota and host metabolism alteration - Qiqiong Li; Jielun Hu; Qixing Nie; Xiao Chang; Qingying Fang; Junhua Xie; Haishan Li; Shaoping Nie (Science China Life Sciences, 2021)

Risks of maternal prepregnancy overweight/obesity, excessive gestational weight gain, and bottle-feeding in infancy rapid weight gain: evidence from a cohort study in China - Shaoping Yang; Hong Mei; Hui Mei; Yan Yang; Na Li; Yafei Tan; Yiming Zhang; Dan Zhang; Yan Zhang; An’na Peng; Bin Zhang (Science China Life Sciences, 2019)

Development of a Self-Recording Per-Minute Precipitation Dataset for China - Xiaohui Ju; Shaoping Huang; Changjun Li; Jun Li; Yunjian Zhan; Shaohua Fan (Journal of Meteorological Research, 2019)

Network Analysis of Depression-Related Transcriptomic Profiles - Xiao Miao; Bin Fan; Rongqun Li; Shaoping Zhang; Honghuang Lin (NeuroMolecular Medicine, 2019)

Mutations of ARX and non-syndromic intellectual disability in Chinese population - Yufei Wu; Huan Zhang; Xiaofen Liu; Zhangyan Shi; Hongling Li; Zhibin Wang; Xiaoyong Jie; Shaoping Huang; Fuchang Zhang; Junlin Li; Kejin Zhang; Xiaocai Gao (Genes & Genomics, 2019)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

The novel Na+/H+ antiporter gene SpNHX1 from Sesuvium portulacastrum confers enhanced salt tolerance to transgenic yeast - Yang Zhou; Chenglong Yang; Yanping Hu; Xiaochang Yin; Ruimei Li; Shaoping Fu; Baibi Zhu; Jianchun Guo; Xingyu Jiang (Acta Physiologiae Plantarum, 2018)

Experimental Study on Displacement Field of Strata Overlying Goaf with Sloping Coal Seam - Shaoping Zhou; Kan Wu; Dawei Zhou; Liang Li; Yuankun Xu (Geotechnical and Geological Engineering, 2016)

Spatial distribution and potential sources of trace metals in insoluble particles of snow from Urumqi, China - Xiaolan Li; Fengqing Jiang; Shaoping Wang; Muyesser Turdi; Zhaoyong Zhang (Environmental Monitoring and Assessment, 2015)

Isolation and characterization of a C-repeat binding factor (CBF)-like gene in cassava (Manihot esculenta Crantz) - Ruimei Li; Yimeng Ji; Jie Fan; Chenglong Yang; Yuan Yao; Yang Zhou; Ruijun Duan; Jiao Liu; Shaoping Fu; Xinwen Hu; Jianchun Guo (Acta Physiologiae Plantarum, 2014)

Antidiabetic and Pancreas-Protective Effects of Zinc Threoninate Chelate in Diabetic Rats may be Associated with its Antioxidative Stress Ability - Kexue Zhu; Shaoping Nie; Chuan Li; Jianqin Huang; Xiaobo Hu; Wenjuan Li; Deming Gong; Mingyong Xie (Biological Trace Element Research, 2013)

Polymer-Mediated Anti-solvent Crystallization of Nitrendipine: Monodispersed Spherical Crystals and Growth Mechanism - Dengning Xia; Mei Ouyang; Jian X. Wu; Yanbo Jiang; Hongyu Piao; Shaoping Sun; Li Zheng; Jukka Rantanen; Fude Cui; Mingshi Yang (Pharmaceutical Research, 2012)

VP15R from infectious spleen and kidney necrosis virus is a non-muscle myosin-II-binding protein - Xiaopeng Xu; Ting Lin; Lichao Huang; Shaoping Weng; Wei Wei; Zhongsheng Li; Ling Lü; Zhijian Huang; Jianguo He (Archives of Virology, 2011)

Relationship between meteorological conditions and natural reproduction behavior of the four famous Chinese carps - Ke Wang; Wengen Liao; Chong Li; Daqing Chen; Shaoping Liu; Xinbin Duan (Environmental Biology of Fishes, 2010)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Transformation of Lead Solid Fraction in the Rhizosphere of Elsholtzia splendens: The Importance of Organic Matter - Jianjun Yang; Shaoping Hu; Xincai Chen; Mingge Yu; Jin Liu; Hang Li; Chaofeng Shen; Jiyan Shi; Yingxu Chen (Water, Air, & Soil Pollution, 2010)

Proteomic characterization of copper stress response in Elsholtzia splendens roots and leaves - Feng Li; Jiyan Shi; Chaofeng Shen; Guangcun Chen; Shaoping Hu; Yingxu Chen (Plant Molecular Biology, 2009)

Changes in abundance of larvae of the four domestic Chinese carps in the middle reach of the Yangtze River, China, before and after closing of the Three Gorges Dam - Xinbin Duan; Shaoping Liu; Mugui Huang; Shunling Qiu; Zhihua Li; Ke Wang; Daqing Chen (Environmental Biology of Fishes, 2009)

Cloning, characterization and expression analysis of a CXCR1-like gene from mandarin fish Siniperca chuatsi - Chao Chen; Zhongsheng Li; Zhicheng Zhou; Zhixin Yin; Siu-Ming Chan; Xiao-Qiang Yu; Shaoping Weng; Jianguo He (Fish Physiology and Biochemistry, 2009)

Genetic diversity in the bronze gudgeon, Coreius heterodon, from the Yangtze River system based on mtDNA sequences of the control region - Li Yan; Dengqiang Wang; Yaoling Fang; Shaoping Liu; Xinbing Duan; Yonghua Chang; Daqing Chen (Environmental Biology of Fishes, 2008)

Distribution of different taste buds and expression of α-gustducin in the barbells of yellow catfish (Pelteobagrus fulvidraco) - Genhua Zhang; Shaoping Deng; Haiyun Zhang; Hongtao Li; Leilei Li (Fish Physiology and Biochemistry, 2006)